2014
DOI: 10.2217/nnm.13.54
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chitosan/Heparin Nanoparticle-Encapsulated Cytolethal Distending Toxin for Gastric Cancer Therapy

Abstract: These findings indicate that chitosan/heparin nanoparticle-encapsulated CdtB could represent a new CdtB delivery strategy for the treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Previous investigations have utilized CDT from Aggregatibacter actinomycetemcomitans for the treatment of human gingival squamous carcinoma and oral cancer cells [19-21]. Recently, our group developed chitosan/heparin nanoparticles for the delivery of C. jejuni CdtB as a potential therapeutic agent for gastric cancer [53]. Our in vivo xenograft experiments in this study further demonstrated that C. jejuni CDT effectively inhibited the growth of radio-resistant PCa (Figure 7).…”
Section: Discussionsupporting
confidence: 63%
“…Previous investigations have utilized CDT from Aggregatibacter actinomycetemcomitans for the treatment of human gingival squamous carcinoma and oral cancer cells [19-21]. Recently, our group developed chitosan/heparin nanoparticles for the delivery of C. jejuni CdtB as a potential therapeutic agent for gastric cancer [53]. Our in vivo xenograft experiments in this study further demonstrated that C. jejuni CDT effectively inhibited the growth of radio-resistant PCa (Figure 7).…”
Section: Discussionsupporting
confidence: 63%
“…Effect of CdtB (rcdtB) protein into gingival squamous cell carcinoma cells using a BioPORTER as an in vitro system for delivery and also effects of cdtB gene transfection with sonoporation on the viability of cells confirmed apoptosis following delivery of those molecules in cells (Nishihara andKoseki, 2004 ,Yamamoto et al, 2004).Cheng-Kuo Lai et all., have attempted to use His-tagged CdtB subunit along with chitosan/heparin nanoparticle vehicle system for delivering transfected into gastric cancer cells. The findings confirmed nanoparticle-CdtB-induced cell death of gastric cancer cells due to DSBs and G2/M cell-cycle arrest, followed by apoptosis (Lai et al, 2014). In another study, Wising C et al (2010) reported that, toxic properties of replication deficient adenovirus type 5 (Ad5) vector expressing CdtB cause loss of cell viability, morphologic changes, and cell cycle arrest on HeLa cells.…”
Section: Discussionsupporting
confidence: 54%
“…Cells were then incubated at 37°C for 24 h and 48 h. The treated cells were harvested and fixed with ice-cold 70% ethanol for 1 h and stained with 20 μg/ml propidium iodide (Sigma-Aldrich) containing 1 mg/ml RNase (Sigma-Aldrich) for 1 h. The stained cells were determined by FACScalibur flow cytometer (Becton-Dickinson, San Jose, CA) and the data were analyzed using Cell Quest software WinMDI (Verity Software House, Topsham, Me) as described previously [30]. …”
Section: Methodsmentioning
confidence: 99%